An economic perspective on small-scale cogeneration systems optimisation - Ferreira, Ana C. M. (2011)
A numerical optimisation method, previously applied to a large cogeneration plant has been adapted for a small-scale unit delivering 125kW of useful heat and 90 to 100kW of electricity. The unit is based on a micro gas-turbine and includes an internal pre-heater (typical of these types of small-scale units) and a WH (Water Heater). The mathematical model yields a non- linear objective function, subject to physical constraints of system operation. The electrical power production is one of the six decision variables that were selected for the optimisation algorithm where the objective function is defined as the maximization of annual worth of the CHP system. A sensitivity analysis was carried out and showed that the relationship between the electricity feed-in tariff and the natural gas price significantly affects the heat to power ratio of the system.